Geographic trends in asthma risk among children and adolescents across climate zones in Australia, 2004–2018 - Jialu Wang; Javier Cortes-Ramirez; Wenbiao Hu (Advances in Climate Change Research, 2025)
Despite the known regional variations in childhood and adolescent asthma prevalence across Australia, the complex interactions between geographic location, climate diversity, and asthma risk patterns remain critically underexplored. This study examined spatial patterns of asthma prevalence among children and adolescents (2004–2018) by analysing data from the Longitudinal Study of Australian Children, categorized according to the Köppen-Geiger climate classification system, which integrates environmental factors such as temperature, humidity, and precipitation patterns to represent broader climatic conditions. We employed spatial clustering, survey-weighted logistic regression, and classification and regression tree analysis to identify region-specific risk factors. Results revealed distinct spatial patterns with ‘high-high’ clusters concentrated in southeastern Australia’s BSk (arid, steppe, cold), Cfa (temperate, no dry season, hot summer), and Cfb (temperate, no dry season, warm summer) climate. Male children (odds ratio (OR): 1.27; 95% confidence interval (CI): 1.06–1.52) with maternal depression (OR: 1.40; 95% CI: 1.16–1.69) and a parental asthma history (OR: 2.96; 95% CI: 2.58–3.41) showed significantly elevated risk, while breastfeeding beyond six months corresponded with reduced risk (OR: 0.73; 95% CI: 0.62–0.86). ‘Low-low’ clusters were observed in the Cfa zone. Risk factor importance varied by climate zone, with breastfeeding duration being most notable in the Aw (tropical, savannah) zone and age 2 emerging as a key threshold in several zones. These findings enable more precise identification of high-risk populations and climate-sensitive regions, supporting the development of targeted preventive strategies and climate-based early warning systems that will enhance asthma management effectiveness and reduce healthcare burdens across Australia.